Parameters used in electrophototherapy for wound healing: A scope review (Research, Society and Development, 2021)
Objective: Point out parameters used for wound healing through electrophototherapeutic modalities in patients with pressure ulcers and diabetics. Methods: We searched for articles in the databases: PubMed, BVS, SciELO and PEDro, published between 2010 and May 2020. Two authors independently analyzed the eligibility criteria using the PEDro Scale. Results: The included studies indicate that electrophototherapeutic resources can be effective in the treatment of pressure and diabetic ulcers and that these resources applied in conjunction with conventional intervention optimize patient improvement. Conclusions: There was a great heterogeneity in the analyzed parameters, the most efficient being the Spectrum Light, with 400 to 800 nm, 0.18 W / cm², 4 minutes, 2 applications per day, for 12 weeks. The LED, with 625, 660, 850 nm, 2.4 J / cm2, 50%, 5 minutes, 3 applications per week, for 8 weeks. LLLT, with 685 nm, 0.05 W / cm², 10 J / cm2, 3 minutes, 6 applications per week, lasting from 2 to 20 weeks. And CAV, with 100 pps, 0.24 or 0.25 A, 154 µs, 100 V, 250 or 360 µC / s, 50 minutes, 5 applications per week, lasting 6 or 8 weeks.